Diffuse hepatocellular carcinoma and splenic atrophy in a cirrhotic patient - Yusuf BAYRAKTAR; Abdurrahman KADAYIFÇI; Ferhun BALKANCI; Şevket RUACAN; Burhan KAYHAN (Turkish Journal of Gastroenterology, 2020)
-